Damage characterisation on PP-hemp/aluminium fibre–metal laminates using acoustic emission - C., Santulli; Nicholas Kuan, Hoo Tien; F., Sarasini; I M, De Rosa; W J, Cantwell (SAGE Publications, 2012)
In this work, type 2024-O aluminium from ALCOA with a nominal thickness of 0.5 mm was stacked on both sides of a hemp polypropylene composite with stacking sequence 1Al/10PP/1H/10PP/1Al. Tensile and planar indentation loading of the fibre–metal laminates so obtained have been followed in real time using acoustic emission monitoring and related to damage characterisation obtained by scanning electron microscopy. The results confirm that natural fibre-based fibre–metal laminates may have significant potential in engineering, whenever an easier recyclability is desirable, although the properties of hemp fibre composite core are likely to affect their performance during loading, especially at stress levels exceeding their elastic limit. Acoustic emission analysis, based on the study of counts, amplitude and duration, confirms that hemp fibre fracture plays a significant role during tensile loading, whilst, during indentation, collapse is originated by the star-shaped cracking of aluminium sheets. The possible improvement of interface strength, with respect to the simple film stacking process adopted for composite manufacturing, would need attention in future work.